Effect of maternal nutritional education and counselling on children’s stunting prevalence in urban informal settlements in Nairobi, Kenya - Nyamasege, CK (Public Health Nutr, 2021)
OBJECTIVE: To determine whether the prevalence of stunting differed between an intervention group and a control group and to identify factors associated with the children’s linear growth. DESIGN: This was a follow-up study of mother–child pairs who participated in a 2012–2015 cluster randomised controlled trial. Linear mixed effects models were performed to model the children’s linear growth and identify the determinants of child linear growth. SETTING: The study was conducted in two slums in Nairobi. The intervention group received monthly nutrition education and counselling (NEC) during pregnancy and infancy period. PARTICIPANTS: A birth cohort of 1004 was followed up every 3 months after delivery to the 13th month. However, as a result of dropouts, a total of 438 mother–child pairs participated during the 55-month follow-up. The loss to follow-up baseline characteristics did not differ from those included for analysis. RESULTS: Length-for-age z-scores decreased from birth to the 13th month, mean –1·42 (sd 2·04), with the control group (33·5 %) reporting a significantly higher prevalence of stunting than the intervention group (28·6 %). Conversely, the scores increased in the 55th month, mean –0·89 (sd 1·04), with significantly more males (16·5 %) stunted in the control group than in the intervention group (8·3 %). Being in the control group, being a male child, often vomiting/regurgitating food, mother’s stature of <154 cm and early weaning were negatively associated with children’s linear growth. CONCLUSIONS: Home-based maternal NEC reduced stunting among under five years; however, the long-term benefits of this intervention on children’s health need to be elucidated.